The Influence of Digital Marketing, Electronic Word of Mouth, and Product Quality on Skincare Product Purchase Intention Through Perceived Authenticity in Generation Z - Risal, M.; Mirna Sari; Safaanjani; Jamilatul Qomariah; Julianitha Aulia Putri (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the effects of digital marketing, electronic word of mouth (E-WOM), and product quality on purchase intention through perceived authenticity among Generation Z skincare consumers using TikTok in East Kalimantan. Using a quantitative survey, data was collected from 280 respondents and analyzed with SEM-PLS. The results indicate that digital marketing and product quality positively influence purchase intention and perceived authenticity. Perceived authenticity also significantly enhances purchase intention and mediates the effects of digital marketing and product quality. However, E-WOM has no significant direct or indirect effect. These findings highlight authenticity as a key driver of consumers’ purchase intention. Keywords: Digital Marketing; Electronic Word of Mouth; Product Quality; Perceived Authenticity; Purchase Intention; TikTok